PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI MEDIATOR PADA PEGAWAI DINAS PERIKANAN KABUPATEN KUTAI TIMUR - Verawaty; Aji Ratna Kusuma; Nanok Fitriyadi; Rizkiawan (Program Studi Manajemen, 2025)
This study aims to determine the effect of employee engagement on employee performance and job satisfaction as a mediator variable among employees at the East Kutai Regency Fisheries Office. A sample of 120 respondents was used. The sampling technique used was non-probability sampling with saturated (census) sampling. Data analysis used in this study was descriptive quantitative, using structural equation modeling (SEM). The results of the t-test showed that employee engagement influenced employee commitment, while employee engagement and job satisfaction influenced employee performance. Employee engagement and employee performance can be mediated by job satisfaction. The first coefficient of determination obtained from the independent variable (X versus Z) in this study was 60.5 percent, and the second coefficient of determination obtained from the independent variables (X & Z versus Y) in this study was 69.9 percent.